Analisis Implementasi Kebijakan Penangkapan Ikan Terukur dalam Permen KP Nomor 28 Tahun 2023: Studi Keadilan Penetapan Pelabuhan Pangkalan bagi Nelayan - Wendy Hendriawan; Didik Suhariyanto; Puguh Aji Hari Setiawan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
As an archipelagic state, Indonesia possesses vast fishery resource potential but faces the threat of overfishing. In response, the government implemented the Measured Fishing (Penangkapan Ikan Terukur or PIT) policy, regulated under Government Regulation Number 11 of 2023 and Ministerial Regulation of Marine Affairs and Fisheries Number 28 of 2023, which includes the mandatory landing of fish at designated base ports. This policy has raised concerns regarding distributive justice due to infrastructure disparities, limited facilities and a disproportionate administrative burden on small-scale fishermen. This research aims to analyze the regulation of base ports in ensuring equitable access and resource distribution, as well as to formulate more just policy frameworks. The method employed is normative legal research using a statutory approach and an analysis based on John Rawls' Theory of Distributive Justice. The findings reveal procedural and economic injustices resulting from the misalignment between legal obligations and infrastructural availability. This condition creates structural discrimination against fishermen in regions with limited facilities. Therefore, a policy reconstruction based on distributive justice is required through the implementation of tiered tariffs, prioritization for small-scale fishermen and the equitable distribution of cold chain facilities to ensure that legal compliance does not disadvantage traditional fishermen.